Rurality, Nigeria's massification policy on access to basic education and turnover causations amongst teachers - Olatunji, Oluwole; Ajayi, S. (Society for the Provision of Education for Rural Australia, 2016)
World Bank’s data indicate 70 per cent of the African population lives in rural areas. Additional evidence made available by the African Development Bank [Africa’s own version of the World Bank] suggests 65 per cent of Africa’s urban dwellers live in slums. This paper relies on these data to conceptualise Africa’s global rurality and issues around access to basic education in Nigeria – as a situation where systemic infrastructure deficit and socio-economic issues constrain access to the delivery of a decent basic education to the populace. Further reflection on the World Bank data shows about one-third of Nigeria’s school-age children are still out of school, and that school attendance was as low as 43 per cent in some regions. Elements of rurality, such as access issues, poverty and a lack of systemic motivation, are the main causes. Thus, confronting the challenges of access to basic education is a major project for the Nigerian government. Several efforts around this have been introduced (since 2004). A larger mass of out-of-school population [i.e. school age and adult population who have not had a chance to access or complete basic education previously] are now able to receive education. The massification efforts [defined as a combination of policies and statutory actions dedicated to a massive increase in student enrolment] have resulted in significant rise in enrolment numbers in elementary and high schools. Enrolments have risen by 31 per cent in elementary schools and doubled in high schools between 2000 and 2010. However, pre-existing issues have often diminished the incentive to achieve the greater goals of massification efforts. Intense poverty, issues relating to access infrastructure, poor resourcing in schools and teachers’ motivation to remain or quit their roles are among the widespread problems. This study reviews literature on one of such issues: causations of teachers’ intention to quit, and the logical relationships between turnover causations and the concept of rurality in the Nigerian basic education policy. Findings on these objectives are critical. Useful contributions are made in this paper to extant body of knowledge on the concept of global rurality by providing framework upon which further (finer-grained) analysis could be conducted to ascertain the statistical relationship between turnover causations and teachers’ demographic variables. Educational administrators and development fund administrators will find the findings useful.